Perlindungan Hukum Bagi Masyarakat Terhadap Dampak Pengadaan Tanah Jalan Tol Ruas Terbanggi Besar Pematang Panggang - Muhammad Alfayyad Ryandika (Publikasi Indonesia, 2022)
The implementation of land for the construction of toll road infrastructure has been regulated in a clear and detailed manner, the stages of land implementation are in accordance with the applicable laws and regulations, but there are several legal problems which are: First, what is the impact on the community. second, when people's rights are fulfilled. Third, what steps has the government taken to protect the affected communities. This study uses a qualitative approach to analyze a phenomenon that is supported by the data obtained by the researcher. The theory used in this research is the theory of public policy, policy evaluation and legal protection. The impacts that occur on the construction of high-rise toll roads – bund roasting loss of land, loss of building property, loss of productive assets, loss of livelihoods, loss of public utility services, loss of public property resources, loss of access to civil services and shared resources, loss of cultural property, displacement of vulnerable groups, changes in social interactions, dust and noise pollution. The government has established a policy to overcome the impacts that occur on the community due to the construction of toll roads and has fulfilled thlocal government in dealing with human resources in order to compete in economic development. The implementation of land for the construction of toll road infrastructure has been regulated in a clear and detailed manner, the stages of land implementation are in accordance with the applicable laws and regulations, but there are several legal problems which are: First, what is the impact on the community. second, when people's rights are fulfilled. Third, what steps has the government taken to protect the affected communities. This study uses a qualitative approach to analyze a phenomenon that is supported by the data obtained by the researcher. The theory used in this research is the theory of public policy, policy evaluation and legal protection. The impacts that occur on the construction of high-rise toll roads – bund roasting loss of land, loss of building property, loss of productive assets, loss of livelihoods, loss of public utility services, loss of public property resources, loss of access to civil services and shared resources, loss of cultural property, displacement of vulnerable groups, changes in social interactions, dust and noise pollution. The government has established a policy to overcome the impacts that occur on the community due to the construction of toll roads and has fulfilled thlocal government in dealing with human resources in order to compete in economic development.